Pengaruh Pupuk Organik pada Pertumbuhan Vegetatif Tanaman Tebu (Saccharum officinarum L.) Varietas GMP 2 dan GMP 3 - Putra, Endriyana; Sudirman, Albertus; Indrawati, Wiwik (Jurnal Agro Industri Perkebunan, 2016)
The sugarcane (Saccharum officinarum L.) is the plant that worth high economical enough, because is the main raw material in manufacture of sugar. One of the efforts to increase the sugarcane production is applying organic fertilizer that can support the growth of sugarcane. The organic fertilizer is fertilizer that's mostly or entirely consist of organic material that from plants or animals that have through the decomposition process, it's can be solid or liquid which is used to supply organic material to improve the physical, chemical and biological soil. It's carried in the garden at Politeknik Negeri Lampung in September 2014 until January 2015. The experiment were performed using a randomized design group (RDG) factorial design which consists of two treatment factor is dosage of organic fertilizer and sugarcane varieties. The first was treatment    dose of organic fertilizer that consists of  5 levels, it?s 0 kg.ha-1 (control), 500 kg.ha-1, 1000 kg.ha-1, 1500 kg.ha-1, and 2000 kg.ha-1. The second factor is a sugarcane varieties, it'sGMP 2 and GMP 3 varieties.  The study aims to get the optimal dose of organic fertilizer (Ghaly Organik), the best sugarcane varieties and knowing the interaction between the treatmenton vegetative growth of sugarcane. The result showed that the optimal dose that was applied on GMP 2 and GMP 3 varieties is 1000 kg.ha-1. GMP 2 Sugarcane varieties have better vegetative growth as compare with GMP 3sugarcane varieties. There is not interaction that happened between treatment dose of organic fertilizer and sugarcane varieties.Keywords : organic fertilizer, sugarcane varieties, vegetative growthPermalink: http://jurnal.polinela.ac.id/index.php/AIP/article/view/44